Aspects affecting the health and safety management and the implementation of measures to reduce vibration exposure in industry - Fisk, Karin ; 0000-0002-4323-6684; Ek, Åsa ; 0000-0002-2377-459X (International Journal of Occupational Safety and Ergonomics, 2025)
Hand-held power tools with high levels of vibration can give rise to hand–arm vibration syndrome, involving chronic nerve and vascular damage. The objective of this study was to identify aspects that could affect the implementation and future use of low-vibration tools in four types of industries: construction, quarrying, steelworks and dental laboratories. Field visits including observations and interviews were conducted in six organizations. Results showed a need to increase knowledge and awareness of vibration exposure and risks in the organizations, as well as a need for increased communication on the topic. Aspects affecting implementation were also user acceptance of new tools (to overcome fear of changes in craftsmanship and conservatism), having a clear and consistent leadership for change with great commitment, and manufacturers ensuring availability of low-vibrating tools. Implementation requires well-thought-out change processes with worker involvement. Customer demand for low-vibrating tools is needed for tool development and supply.
Keywords: Hand–arm vibration; Risk awareness; Tools; Holistic approach; Qualitative